Case Report: Perivascular epithelioid tumors of the gastrointestinal tract - Hui Yan; Shuhui Zhang; Ying Ba; Kun Li; Guoling Gao; Yanmin Li; Yan Zhang; Chengxia Liu; Ning Shi (Frontiers in Oncology, 2023)
BackgroundPerivascular epithelioid cell tumor of the gastrointestinal tract (GI PEComa) is a rare mesenchymal neoplasm. GI PEComa is mostly observed in the colon and has a marked middle-aged female predominance. PEComa has no typical clinical or imaging manifestations or endoscopic characteristics. Therefore, the diagnosis of this disease mostly relies on pathological findings. HMB-45 is a sensitive immune marker of PEComa.Case presentationWe reported a case of a middle-aged female with sigmoid colon PEComa. To exclude carcinogenesis, the large basal polyp in the sigmoid colon was removed by endoscopic mucosal resection (EMR). Immunohistochemistry analysis results showed that this lesion expressed HMB-45, which is a characteristic melanin marker of PEComa. Finally, the lesion was diagnosed as sigmoid colon PEComa. At the time of submission of this report, surgical resection was the primary treatment for PEComa. Though the characteristics of tumor biology and clinical behavior in PEComa are not clear, the boundary is clear, and the tumor can be completely removed. However, close follow-up is required after the surgery because of the lesion’s undetermined benign and malignant nature.ConclusionThe present case study emphasizes the importance of pathological diagnosis. Therefore, upon finding gastrointestinal polyps with a mucosal ulcer under endoscopy, the GI PEComa diagnosis should be considered. It is necessary to detect the characteristic melanin markers of PEComa. Due to the rarity of these cases, challenges are faced in diagnosing and treating PEComa.